A Comparative study on the photocatalytic degradation of industrial dyes using modified commercial and synthesized TiO2 photocatalysts - Rahman, Mohammed Mastabur; Choudhury, Fatema Akthar; Hossain, Md Delowar; Chowdhury, Md Namwarul Islam; Mohsin, Sadia; Hasan, Md Mehdi; Uddin, Md Fakar; Sarker, Niloy Chandra (Journal of Chemical Engineering, 2014)
Commercial and Synthesized titanium di oxide (TiO2) prepared by conventional sol-gel method, are modified to degrade industrial dyes. Modification is done on bare TiO2 and TiO2 doped with various doping agents (activated charcoal/silicon dioxide/zinc oxide), followed by thermal treatments. The role of thermal treatments and doping effects on the efficiency of TiO2 photocatalysts are highlighted and evaluated by decoloration of Methylene Blue in aqueous solution under UV and Visible light irradiation for both systems. The results revealed that increase in calcination temperature up to optimum level enhances the photocatalytic activities of the samples and doping narrows the band gap and makes the samples visible light responsive. This study also showed that activated charcoal (AC) doped TiO2 photocatalyst is a promising one under Visible light and is thus used to degrade other dyes such as Crystal Violet and Rhodamine B. The obtained experimental data are used to study four different kinetic models: Zero order, Pseudo first order, Parabolic diffusion and Modified Freundlich model. The best fit of the experimental data are obtained by Pseudo first order and Modified Freundlich models. DOI: http://dx.doi.org/10.3329/jce.v27i2.17805 Journal of Chemical Engineering, IEB Vol. ChE. 27, No. 2, December 2012: 65-71